THE IMPLEMENTATION OF PROMOTIONAL STRATEGIES VIA TIKTOK SOCIAL MEDIA TO INCREASE SALES REVENUE AT FAT HUNT SURABAYA - Putri, Ossa Yuansah; Kusuma, Yandra Bara (Penelitian dan Pengembangan Ilmu, 2025)
This research discusses the implementation of promotional strategies through TikTok social media in increasing sales turnover at Kedai Fat Hunt Surabaya. TikTok becomes a platform which is effective in reaching a wide audience through creative and interactive content. Data collection techniques were carried out through in-depth interviews, observation and documentation with a descriptive qualitative approach. The research results show that active and consistent use of TikTok can increase brand awareness through viral content, live streaming, and collaborations with influencers. This strategy had a direct impact on increasing turnover, which experienced a significant spike after promotional content succeeded in attracting the attention of a large audience. However, this research also found challenges in maintaining viral trends and limited technical understanding in optimizing TikTok features. The research results confirm that the use of appropriate promotional strategies on TikTok can be a major factor in increasing the competitiveness of MSMEs and expanding market reach.